2008
DOI: 10.7326/0003-4819-148-10-200805200-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Clinical Uncertainty in Treatment Decisions for Diabetic Patients with Uncontrolled Blood Pressure

Abstract: Approximately 50% of diabetic patients presenting with a substantially elevated triage blood pressure received treatment change at the visit. Clinical uncertainty about the true blood pressure value was a prominent reason that providers did not intensify therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
149
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 151 publications
(162 citation statements)
references
References 43 publications
8
149
4
Order By: Relevance
“…36 Others have determined that patients with mental health conditions or chronic pain are at risk for receiving suboptimal care for their hypertension, diabetes, heart failure, arthritis, and chronic obstructive pulmonary disease. 31,[36][37][38][39][40] Other studies, however, suggest that these patterns are not universal. For example, patients with serious mental health conditions sometimes receive more intensive monitoring of their other chronic conditions.…”
Section: The Relationship Between Multimorbidity and Quality Of Carementioning
confidence: 99%
“…36 Others have determined that patients with mental health conditions or chronic pain are at risk for receiving suboptimal care for their hypertension, diabetes, heart failure, arthritis, and chronic obstructive pulmonary disease. 31,[36][37][38][39][40] Other studies, however, suggest that these patterns are not universal. For example, patients with serious mental health conditions sometimes receive more intensive monitoring of their other chronic conditions.…”
Section: The Relationship Between Multimorbidity and Quality Of Carementioning
confidence: 99%
“…[5][6][7][8] One such study used a conceptual model to systematically identify provider factors associated with a lower likelihood of medication intensification in hypertensive patients with diabetes mellitus. 9 These factors included reported clinical uncertainty regarding BP measurements, competing demands during clinic appointments, inappropriate physician BP goals, lack of timely follow-up of elevated BP, and concern for patient treatment nonadherence.…”
mentioning
confidence: 99%
“…Moreover, the VA has served as a bellwether and model system for evaluating many quality issues with wide applicability. 26,44 In summary, we found that there was a clinically important drop in prescribing rates in older age groups that was not explained by a wide variety of factors, but that these differences were more difficult to detect after accounting for reasons cited in the clinical chart for non-prescribing. Patients in the upper reaches of age are different from their younger counterparts, and unique considerations need to be evaluated in making treatment decisions for this vulnerable group.…”
Section: 41-43mentioning
confidence: 91%